The curious incident of the dog in the night-time - Haddon, Mark 1962- (Doubleday, 2003)
Despite his overwhelming fear of interacting with people, Christopher, a mathematically-gifted, autistic, fifteen-year-old boy, decides to investigate the murder of a neighbor's dog and uncovers secret information about his mother.